The Impact of Digitalization on Green Total Factor Productivity of Petrochemical Enterprises - Qiang MA; Min XU; Ling WANG (Liaoning Shiyou Huagong Daxue xuebao)
The petrochemical industry is an important pillar industry in China, which is related to the security and stability of the industrial and supply chains, green and low⁃carbon development, and the improvement of people's well⁃being. By matching macro⁃level urban digitalization data with micro⁃level petrochemical enterprise data from 2012 to 2021, an empirical analysis was conducted to examine the impact of digitalization on the green total factor productivity of petrochemical enterprises. Additionally, the mechanisms through which digitalization enhances the green total factor productivity of petrochemical enterprises were investigated. Research has found that: Digitization has significantly improved the green total factor productivity of petrochemical enterprises; for the eastern region, regions with higher levels of digitalization, and petrochemical enterprises with smaller scale and state⁃owned property rights, digitalization has a greater impact on improving their green total factor productivity; the mechanism of digitalization to enhance the green total factor productivity of petrochemical enterprises is to enhance regional innovation, promote green innovation of enterprises, and accelerate digital transformation of enterprises. Finally, suggestions are proposed to actively embrace digitalization, formulate differentiated development strategies, and leverage the leading role of state⁃owned enterprises, aiming to provide reference and guidance for improving green total factor productivity of petrochemical enterprises in China.